Minat Belajar Siswa Pada Pembelajaran Daring Kelas IV SDN Kamulan 02 Kecamatan Talun Kabupaten Blitar - Ria Fajrin Rizqy Ana (Universitas PGRI Adi Buana Surabaya, 2021)
Interest in learning is an impulse that grows from within students to improve study habits. The problem that occurs online learning is that students are less active and feel bored in following the learning process. Lack of interest in student learning in collecting assignments given by the teacher. This study aims to analyze students' interest in learning during a pandemic. Based on the results of the study, it was obtained that students' interest in learning in online learning got a score of 72% in the high category with reference to 4 indicators, namely the first indicator of student interest in learning is feeling happy, the second indicator is student interest, the third indicator is attention in learning, indicator the fourth is engagement